ปัจจัยเชิงสาเหตุของพฤติกรรมการดูแลสุขภาพของข้าราชการครู อำเภอเมือง จังหวัดเชียงใหม่ - กัญญาภัค คำดา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The Objectives of this research were to study the level of attitude toward health care, health perception, school environment perception, health information perception, and health care behaviors, and to examine factors effecting health care behaviors among government teachers in Mueang District, Chiang Mai Province. The samples were 251 government teachers, using simple random sampling method. The research instrument used for study is questionnaire. The data were analyzed using descriptive statistics and causal structural models. The most of the sample had the mean scores of the attitude towards health care at the highest level. While the health perception, school environment perception, health information perception, and health care behaviors had a high level of average values. In addition, the study of causal factors of health care behaviors of government teachers in Mueang District, Chiang Mai Province found that the attitude toward health care, health perception, school environment perception and health information perception significantly influenced the health care behaviors of government teachers in Mueang District, Chiang Mai Province at the .05 level. Moreover, the result showed that all variables able to explain the variance of health care behaviors 56 %.